Quantum Dynamics Study of $H$ Exchange Reaction of $H'(^2S) + CH(X^2Π) → H(^2S) + CH'(X^2Π)$ and Isotope Reactions of $H(^2S)+CH(X^2Π)→C(^1D)+H_2(X^1\sum^+_g)$ (Journal of Atomic and Molecular Sciences, 2018)
By using the time-dependent quantum wave packet method, we report a detaileddynamics study of H exchange reaction $H'(²S) + CH(X²Π) → H(²S) + CH'(X²Π)$ and the isotope effects of $H(²S) + CH(X²Π) → C(¹D) + H_2(X¹Σ^+_g)$ reaction on the 11ABHL potential energy surface. The reaction probabilities and integral cross sectionshave been obtained for the initial states $v = 0$ and $j = 1$ of the reactant molecules. Thedense resonance structures in the reaction probabilities at all total angular momentumsindicate complex-forming mechanisms for both $C + H_2$ and $H + CH$ products. A comparisonbetween the results from centrifugal sudden approximation and those fromclose-coupled calculations demonstrates that the Coriolis coupling effects get moreand more pronounced with increasing of $J$ for both $H$ exchange reaction and $CH$ decayreaction. The isotopic $D$ substitution of reactant significantly influences the $CH$ decay reaction. Moreover, it is revealed that the dynamical features such as partialwave contributions to the cross section are substantially different for these two channels.